(untitled) (Global Journal of Management and Business Research, 2013)
Coal is a vital source of energy in India. Major portion of energy requirement in India fulfill by coal based thermal power plant. Price of electricity indirectly depends on raw material (coal). In India coal trading generally done on over the counter basis, in which price of coal is depend on settlement price of coal as per the quality of coal. Coal price is generally calculated on certain parameter moisture content, calorific value, ash content, sulfur content. India supplier settles coal prices on some formula to adjust coal price. The object of this paper is to highlight the price adjustment formula which buyer and seller used to calculate price settlement for their contract agreement. Price of coal is generally decided by their calorific value, moisture content, ash content and sulphur content in coal. So for the adjustment in price Coal supplier and buyer use some formula as per quality to adjust quantity. The aim of this paper is to amend existed formula, and to give innovative approach to implement a price adjustment formula of coal as per the quality bases.